Heavy Metal (Ni, Fe) Concentration in Water and Histopathological of Marine Fish in the Obi Island, Indonesia. - Aris, Muhammad; Tamrin, Tamrin (Jurnal Ilmiah PLATAX, 2020)
This study aims to determine the content of nickel (Ni) and iron (Fe) as well as histopathological analysis of marine fish in Obi Island waters as a bioindicator of pollution. Besides, water quality conditions were carried out in-situ and ex-situ observations. The parameters observed were temperature, brightness, salinity, pH, dissolved oxygen, nitrate, orthophosphate, ammonia, iron (Fe), and nickel (Ni). The results showed the temperature range between 26.48 â„ƒ to 27.99 â„ƒ below the quality standard or low temperature. The brightness of the relationship between 12 m and 13 m is under quality standards. The salinity range between 31.01 ppt to 32.13 ppt below the quality standard. The pH range is from 8.6 to 8.7 in high or alkaline conditions. Ammonia range between 0.4 mg / L to 0.7 mg / L exceeds the quality standard. The range of nitrate between 0.009 mg / L to 0.012 mg / L exceeds the quality standard. The range of phosphate between 0.016 mg / L to 0.019 mg / L exceeds the quality standard. The DO range between 3.68 mg / L to 3.77 mg / L lower than the quality standard. The metal range of 0.6 mg / L to 0.9 mg / L exceeds the quality standard. The range of Ni metal between 0.06 mg / L to 0.09 mg / L exceeds the quality standard. Histopathological analysis showed that the liver had a hemorrhage, degeneration of blood vessels, vacuolate degeneration, necrosis, or cell death. The muscles experience edema, degeneration of muscle fibers, atrophy of muscle bundles, vacuolar degeneration of muscle Bundles, hemorrhage, infiltration of lymphocytes, and necrosis. The intestine experience infiltration of lymphocytes, melanomacrophages, and necrosis. While P. tayenus fish ovaries showed necrosis structure oocytes. This research can be a reference for warning of heavy metal pollution in Obi Island waters, binding to the nature of heavy metals that can accumulate in fish tissue. Keywords: Water quality; Heavy Metal; Pollution; Histopathological; Obi Island.